Civil Society and State-Corporate Crime: A Case Study of Ivory Coast. (1st October 2014) - ,
Abstract : The claims that any civil society organization (CSO) must make to be able to censure states and corporations effectively require a degree of credibility in the eyes of those sections of society that it hopes to influence. Taking the example of the CSO reaction to toxic waste dumping in Ivory Coast, this article seeks to problematize the role of civil society in censuring and controlling crimes committed by governments and corporations. Domestic Ivorian non-governmental organizations (NGOs) were discovered to have little capacity to expose, control, constrain or sanction large-scale state-corporate crime, and the newly created victims' organizations —— claiming to be genuine CSOs —— became involved in the ""commodification of victimhood"" for profit.